RANCANG BANGUN SISTEM PAKAR DIAGNOSA PENYAKIT SAPI DENGAN METODE DEMPSTER-SHAFER BERBASIS WEB - Salistiwa, Harry (Jurusan Informatika Universitas Tanjungpura, 2015)
Abstract – Farmer’s knowledge about cow disease is still low, beside it is very important for achieve healthy meat. Cow diseases are caused by viruses, bacteria, parasite,and reproductive disorders. it can affect the quality of the meat and milk that led to the decrease in production. To minimize those impact, needs some early treatment to prevent loss. Expert system is one of the solution to diagnose the disease based on symptoms suffered by cows. In this research an expert system created by applying Dempster-Shafer. Applications developed for determining diseases in cows only concerned to the symptoms experienced by the cow. By applying the method of Dempster-Shafer, we may obtained values possible interference illnesses experienced by the cow. System generated may handle the data management and diagnosis of disease with a level of confidence 90%.